Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.21608/jfds.2018.36027
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of some Chicken Edible Internal Organs and Wheat Germ in Production of Sausage

Abstract: Relatively huge amounts of wheat germ are produced annually as a by-product of wheat milling industry in Egypt. Wheat germ had high amounts of protein, ash, fat, carbohydrates and bioactive compounds. The aim of the work was to study the possibility of using chicken's gizzard and liver in production of sausage and effect of substitution of gizzards and liver meat by wheat germ at levels 5, 10, 15 and 20% on proximate composition, physical properties, sensory characteristics and microbiological criteria and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…One of the studies reported an increase in total ash or mineral content by adding chicken liver to sausages. El-Sayed et al (2018) reported an increase from 3.4% to 7.7%, from 0% to 20% of chicken liver addition, respectively. This justifies the ameliorating nutritional content of formulated chicken nuggets with beef and chicken liver supplementation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the studies reported an increase in total ash or mineral content by adding chicken liver to sausages. El-Sayed et al (2018) reported an increase from 3.4% to 7.7%, from 0% to 20% of chicken liver addition, respectively. This justifies the ameliorating nutritional content of formulated chicken nuggets with beef and chicken liver supplementation.…”
Section: Resultsmentioning
confidence: 95%
“…Meat byproducts, predominantly liver, can increase the food item’s overall fat and protein content ( Bujak, 2015 ). Adding chicken liver meat to sausages also increased the overall protein content of the sausages from 34.6% to 37.9% ( El-Sayed et al, 2018 ). The same results were observed when beef liver in powdered form was added to cakes and cookies, resulting in increased protein content and increased beef liver powder concentration ( Folorunso and Ayooluwa, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…10 ), are rich sources of essential nutrients and polyunsaturated fatty acids [ 102 ]. In comparison with other tissues, El-Sayed, Farag [ 103 ] found that the liver and gizzard are the best sources of high-quality protein. A high-protein diet has been demonstrated to boost metabolism, control appetite, and enhance muscle growth and preservation during weight reduction [ 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, duck gizzard peptides can provide a plentiful source of natural antioxidants for applications in the food industry [ 116 ]. The gizzard is a low-fat, high-protein organ that has great natural levels of iron and zinc [ 103 ]. These nutrients support a healthy immune system, promote wound healing, and aid in cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato juices can be fermented with selected species of Lactobacillus, such as L. plantarum, L. bulgaricus, as the probiotic microorganisms, either single strain or as a mixed culture. Tomato juice fermented with lactobacilli can be developed as a potential probiotic product and may additionally bene t to consumers searching for an alternative beverage to substitute fermented dairy products for lactose-allergic human beings and vegetarians [11]. In carrot juices three strains of Bi dobacterium (B. lactis Bb-12, B. bi dum B7.1, and B3.2) showed considerable amount of biochemical activities in carrot juices though during fermentation 15% − 45% of carotenoids specially αcarotenoid and β-carotenoid were degraded as per the strain used [12].…”
Section: Introductionmentioning
confidence: 99%